ETYMOLOGICAL AND SEMANTIC FEATURES OF THE ADDRESS UNIT “FUQARO” (CITIZEN) USED IN KHOREZM FOLKLORE TEXTS - Ruzmatova Nargiza Ollashukur kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the use of the word “fuqaro” (citizen), found in Khorezm folklore texts, as an address unit, as well as the etymological origin, historical meaning, and semantic changes of this lexeme. It also examines the features of the word’s usage in folklore texts and aspects related to its meaning today.